Komunikasi Gender Dan Hubungannya Dengan Kepuasan Kerja Karyawan (Gender Communication Related Employees Job Satisfaction) - Putri Asih Sulistiyo; Aida Vitayala Hubeis; Krishnarini Matindas (Jurnal Komunikasi Pembangunan, 2016)
Harding and Hills’s standpoint theory said that human perspectives are shaped by their social and political experiences. Gender is a social construction that acquired through interaction and changes over times. Based on that theory, this study used to analyze are the rapid increased of woman labour, gender equitymovement in economic development, may affect the the traditional view about how women and men should act and communicate, and established the new meaning of masculinity and feminity in workplace area. The conclusion showed that gender inequity still exist toward women. Women’s job position and the level of gender communication based on dimensional stereotype, discrimination, subordination, and sexual harassment are worse than men, but yet women showed no complains and reported the same level of job satisfaction compared men.Keywords: gender, communication, job satisfaction